Determination of Amatoxins in Lepiota brunneoincarnata and Lepiota venenata by High-Performance Liquid Chromatography Coupled with Mass Spectrometry. Issue 3 (3rd May 2020) - Long, Pan; Fan, Fengxia; Xu, Bin; He, Zhengmi; Su, Yuting; Zhang, Ping; Xie, Jianwei; Chen, Zuohong
Abstract: Three hepatic failure poisoning incidents caused by Lepiota brunneoincarnata and Lepiota venenata mushrooms have been occurred in China in 2017, L. venenata has been described as a new species. However, the cyclopeptide toxins of these lethal mushrooms remain poorly understood. In this study, the composition and content of amatoxins in L. brunneoincarnata and L. venenata are analyzed and compared, the analysis of composition and content of amatoxins in L. venenata are reported for the first time. The results showed that β-amanitin (β-AMA), α-amanitin (α-AMA), amanin, and amaninamide were identified in L. brunneoincarnata, and α-AMA, amanin II (an analog of amanin), and an unknown compound were identified in L. venenata . The differences between L. brunneoincarnata and L. venenata in the identified compounds provide chemical evidence for L. venenata as a new species. Quantitative analysis shows that α-AMA concentrations in L. brunneoincarnata and L. venenata were 0.72–1.97 mg/g dry weight, β-AMA concentrations in L. brunneoincarnata were 0.57–0.94 mg/g dry weight, and β-AMA was absent in L. venenata .